2007
DOI: 10.1073/pnas.0706564104
|View full text |Cite
|
Sign up to set email alerts
|

DNA transposition target immunity and the determinants of the MuB distribution patterns on DNA

Abstract: MuB, an ATP-dependent DNA-binding protein, is critical for the selection of target sites on the host chromosome during the phage Mu transposition. We developed a multichannel fluidic system to study the MuB-DNA interaction dynamics at the single DNA molecule level by total internal reflection fluorescence microscopy. We analyzed the distribution of MuB along DNA during the assembly and disassembly of MuB polymers on immobilized DNA molecules. The results reveal the absence of a significant correlation of MuB p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…MuB binding is influenced by the A/T content of DNA in vitro (Greene and Mizuuchi 2004; Tan et al 2007; Ge and Harshey 2008). However, genes with a high frequency of CGG are preferred Mu targets in vivo (Manna et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…MuB binding is influenced by the A/T content of DNA in vitro (Greene and Mizuuchi 2004; Tan et al 2007; Ge and Harshey 2008). However, genes with a high frequency of CGG are preferred Mu targets in vivo (Manna et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…3C) (34), which hydrolyzes ATP for target selection; both activities are stimulated by MuA (9). MuB forms ATP-dependent helical filaments, with or without DNA (34, 95), and has been reported to exhibit a tendency to form larger filaments on A/T-rich DNA (95, 96). Single-particle EM imaging of MuB assembled on DNA, found that MuB-ATP forms a solenoid-like filament, with DNA bound in the axial channel (34).…”
Section: Target Site Selectionmentioning
confidence: 99%
“…Unlike a RecA filament which extends and unwinds DNA and promotes homology search and strand exchange within the filament, 31 the MuB filament does not appear to change DNA twist (our unpublished data; see also Ref. 22), and is apparently refractory to Mu integration inside the filament. Comparison of the data in Fig.…”
Section: Role Of the Mub Filamentmentioning
confidence: 99%